Business Strategy Analysis at the Puncak Mas Destination in Bandar Lampung City - Ira Anggraini; Selfia Alke Mega (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Because the development of tourism destinations causes tighter business competition, an analysis is needed that is able to explain what companies must do to help increase the number of visitors. Puncak Mas Tourism in the city of Bandar Lampung does not pay attention to the wider visitor segment, this is because ticket prices are not competitive. So this research aims to increase tourist visitors to Puncak Mas Bandar Lampung by applying the SWOT analysis research approach/method (strengths, weaknesses, opportunities, threats). By analyzing the company's internal and external factors and making comparisons between research objects and competitors, we can gain in-depth knowledge about the company's internal and external conditions and compare them with competitors. This study also utilized descriptive research methods, where data was collected through an interview process in the form of a list of questions to the owners of the Puncak Mas tourist destination in the city of Bandar Lampung and its competitors. The research results based on the analysis of a combination of SWOT matrix strategies at the Puncak Mas Bandar Lampung destination obtained Strengths-Opportunities (5.11), Strengths-Threats (2.59), Weakness Opportunities (3.79), Weakness-Threats (1.27).